Quality Improvement Strategy for Strengthening Higher Education Competitiveness (Studies at the College of Economics in East Java) - Fariz Fariz (Khazanah Sosial, 2022)
The challenge for Indonesia in the current era is to prepare itself for economic, business and education activities. One of them is strengthening the competitiveness of higher education, by increasing its quality. The purpose of this study was to analyze and obtain an overview of strategies regarding Quality Improvement for Strengthening Higher Education Competitiveness (Studies at the College of Economics in East Java). The method used in this research is descriptive method with a qualitative approach. The results showed that the implementation of academic services carried out by all components of college including lecturers, staff and academic staff showed a change towards better improvement, in terms of human resource management, as well as supporting facilities that support the implementation of improving the quality of academic services. Higher education institutions need to control the quality of activities carried out at stages in the management process which include input, process, output and stakeholder satisfaction. Service quality improvement can be implemented by implementing the service quality management process, improving and strengthening the curriculum, updating and improving learning facilities, improving quality qualifications and the number of human resources tailored to the needs in college.Â